Development of a novel smoke-flavoured trout product: An approach to sodium reduction and shelf life assessment. (October 2017) - Rizo, Arantxa; Fuentes, Ana; Fernández-Segovia, Isabel; Barat, José M.
Abstract: This work aimed to develop a reduced sodium smoke-flavoured trout product with similar physico-chemical traits and sensory quality to commercial smoked trout. In a first phase, a reduced sodium smoke-flavoured trout product was developed by a novel smoke-flavouring process using water vapour permeable bags. In a second phase, the obtained product's microbial and physico-chemical quality was evaluated for 42 cold storage days. A smoke-flavoured trout product with similar physico-chemical characteristics and sensory acceptance to commercial smoked trout was achieved through smoke-flavouring with water vapour permeable bags. Partial substitution of NaCl for KCl led to a 42% sodium reduction in the smoke-flavoured trout and did not affect its physico-chemical traits, sensory attributes and hygienic quality throughout the storage. During shelf life study, no sample exceeded the limits of acceptance proposed for physico-chemical and microbial parameters, except for mesophilic bacteria, which limited the product shelf life to 1 month. Highlights: A novel reduced sodium smoke-flavoured trout product was obtained. 42% Na + reduction was achieved without affecting sensory traits. Replacing NaCl with KCl did not affect physico-chemical and sensory quality. The reduced sodium smoke-flavoured trout shelf life was around 30 days.